CORPORATE SOCIAL RESPONSIBILITY DAN CORPORATE FINANCIAL PERFORMANCE: INTELLECTUAL CAPITAL SEBAGAI VARIABEL MEDIASI - Machmuddah, Zaky; Oktafiyani, Melati; Titisari, Kartika Hendra (Jurnal Riset Akuntansi (JUARA), 2018)
Corporate Social Responsibility Practice, intellectual capital and corporate financial performance are the main issues of the research. The aims of the current research are to prove the effect of Corporate Social Responsibility Practice on Corporate Financial Performance with IC as a mediating variable. All companies listed in Indonesian Stock Exchange, from 2012-2014 are the population of the research. The total of research samples are 21 companies with 63 annual reports conducted by using purposive sampling method. Data analysis used is warpPLS version 4.0 with direct effect models and indirect effect models. The research findings indicated that Corporate Social Responsibility Practice positively and significantly affected to Intellectual Capital, Corporate Social Responsibility Practice positively and significantly affected to Corporate Financial Performance, Intellectual Capital positively and significantly affected to Corporate Financial Performance and Intellectual Capital mediated the effect of Corporate Social Responsibility Practice to Corporate Financial Performance. The practical implication of the research is to give suggestions to all companies about the role of Corporate Social Responsibility Practice and intellectual capital to increase Corporate Financial Performance. It can be used to companies to increase the Corporate Financial Performance.